How can mobile SMS communication support and enhance a first year undergraduate learning environment? - Geraldine Jones; Gabriele Edwards; Alan Reid (Association for Learning Technology, 2009)
In this paper we discuss a case study investigating how the academic and personal development of first year students on an undergraduate sports education degree can be supported and enhanced with mobile SMS (Short Message Service) communication. SMS-based technologies were introduced in response to students' particular needs (in transition to Higher Education) and characteristics (adept mobile communicators). Despite being unaccustomed to using their mobile phones for academic study, students willingly accepted SMS communication with their tutor via a texting management service. This communication was used in concert and integrated with a more traditional learning and teaching context (lectures and a virtual learning environment). Drawing on evidence from two student surveys, focus groups and a tutor's journal, we illustrate how mobile SMS communication has influenced the student learning experience. Taking a holistic view of the learning environment we use Laurillard's (2002) conversational framework (Laurillard, D. 2002. Rethinking university teaching: a framework for the effective use of learning technologies. 2nd edition. London: Routledge.) to analyse and discuss the role of texting in supporting student transition to higher education.